ANALISIS PENGARUH QUALITV OF WORK LIFE (QWL) DAN MODAL PSIKOLOGI TERHADAP KINERJA DENGAN MODERASI PERSON ORGANIZATION FIT (PO FIT) (Studi Pada Sekretariat Dacrah Kabupatcn Pati) - Handayani, Sri; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2017)
This stuth aims to examine and anali.e the effect ql Quality 01’ Work Ltfr IQWLI and Capital rn the Performance Psychology iith moderation Perso,, Organization fit (PO Fit) in Pati regency Regional Secretarial. The population ¡n this stuth a number of 165 people. The sample using purposive sampling techniques. so that the sanrple in this study a number of ¡05 respondents. The data Err the text . inducks u model lest, t test and mod.. attun. C’ompilatiun a/data using queslionnairex, which in raiidi’ and reliability, Ba.sed on the results of study show that the Qua!irr nf iInrk Líe (QWL) positive and signficcrn, Impact on performance. (apital Psvcholog,i’ positive and signiji ca,,! impact on performance, Person Organization Fi: (PO Fit ix not a twriahle moderating influence of Quali of Work Lfe i’QWL) to Pci formance as well ax the influence of Psychological Capital on performance.